PENGARUH CUSTOMER EXPERIENCE, EASE OF USE, DAN TRUST TERHADAP LOYALITAS E-COMMERCE - Rianto, Muhammad Iqbal; Hapsari, Raditha Dwi Vata (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
In the midst of such intense competition, e-commerce companies must be keen to see every opportunity to grow and effectively come up with new breakthroughs so that people do not move and continue to transact with the company. Since its inception in 2012, Lazada has created a good flow of e-commerce business in Indonesia. However, during 2018-2020, Lazada's monthly website visits always ranked fourth. This study aims to analyze the factors that affect Lazada e-commerce loyalty. The type of research used is explanatory research. This study uses 110 respondents, who are Lazada E-Commerce customers. The sampling technique used is a non-probability sampling technique, namely purposive sampling. Data analysis technique using SmartPLS 3.3. The results of this study indicate that customer experience has a positive and significant effect on loyalty, ease of use has a positive and significant effect on loyalty, and trust has a positive and significant effect on loyalty.